2017
DOI: 10.1103/physrevd.96.105017
|View full text |Cite
|
Sign up to set email alerts
|

Vacua and walls of mass-deformed Kähler nonlinear sigma models on SO(2N)/U(N)

Abstract: We construct walls of mass-deformed Kähler nonlinear sigma models on SO(2N )/U (N ), by using the moduli matrix formalism and the simple roots of SO(2N ). Penetrable walls are observed in the nonlinear sigma models on SO(2N )/U (N )

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…It is observed in [3] that the configurations of vacua and elementary walls of the mass-deformed nonlinear sigma models on SO(2N )/U (N ) and Sp(N )/U (N ) exhibit distinguishable features as the lengths of the simple roots of SO(2N ) are the same whereas the lengths of the simple roots of U Sp(2N ) are not all the same. These properties would contribute to three-pronged junctions of the models since three-pronged junctions are formed by compressed walls as well as elementary walls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed in [3] that the configurations of vacua and elementary walls of the mass-deformed nonlinear sigma models on SO(2N )/U (N ) and Sp(N )/U (N ) exhibit distinguishable features as the lengths of the simple roots of SO(2N ) are the same whereas the lengths of the simple roots of U Sp(2N ) are not all the same. These properties would contribute to three-pronged junctions of the models since three-pronged junctions are formed by compressed walls as well as elementary walls.…”
Section: Discussionmentioning
confidence: 99%
“…Kink solutions of the nonlinear sigma models on SO(2N )/U (N ) and Sp(N )/U (N ), which are quadrics in the Grassmann manifold G 2N,N are studied in [5,3]. It is shown that the moduli spaces of vacua and walls are SO(2N )/U (N ) and Sp(N )/U (N ) respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation made in [9] should be useful not only for constructing BPS walls, but also for analysing supersymmetric models, which have 1/1 vacua, 1/2 BPS objects and 1/4 BPS objects since the moduli matrix formalism produces exact solutions in the mass-deformed nonlinear sigma models on the compact Hermitian symmetric spaces of the quotient with respect to the gauge group.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method is proposed to construct three-pronged junctions of the mass-deformed nonlinear sigma models on the Grassmann manifold [20]. The pictorial representation, which is introduced by [9], is applied to vacua and walls of mass-deformed nonlinear sigma models on the Grassmann manifold. The vacua and the walls of the mass-deformed nonlinear sigma models on G N F ,N C with (N F , N C ) = (4, 2),(5, 2),(5, 3),(6, 2), (6, 3), (6,4) are explicitly shown in the representation.…”
Section: Introductionmentioning
confidence: 99%